AN EXAMINATION OF INACTIVATION EFFICACY OF NACL AND BORIC ACID ON BACTERIA ISOLATED FROM SALTED HIDES - (:unkn) unknown (AMER LEATHER CHEMISTS ASSOC, 2013)
Due to isolation of bacteria in high number on the salt-pack cured hides in our recent studies, the inactivation efficacy of different concentrations of NaCl and Boric acid, used as curing agents, on Gram-positive (Staphylococcus epidermidis and Enterococcus faecium), Gram-positive endospore forming bacteria (Bacillus pumilus and Bacillus licheniformis), Gram-negative bacteria (Pseudomonas aeruginosa and Pseudomonas fluorescens) and the mixed culture of these isolates was investigated. These proteolytic and lipolytic bacteria were isolated from the salted hides. Inactivation efficacy of NaCl and Boric acid on the bacteria was examined in Nutrient Broth and Nutrient Agar media containing 5%, 10%, 15%, 20%, 25%, 30% NaCl; 1%, 2%, 3%, 4%, 5%, 7% Boric acid; and both 5%, 10%, 15% NaCl and 1% Boric acid. In addition, the test bacteria were inoculated in Nutrient Broth containing 20%, 25%, 30% NaCl and 2%, 3%, 4%, 5%, 7% Boric acid and incubated for 24 hours at 35 C. Afterwards, viable bacterial cell counts were determined on NaCl-free Nutrient Agar and boric acid-free Nutrient Agar. The data obtained from this study showed that bacterial growth was prevented by high concentrations of NaCl and boric acid, but the bacteria were still alive and complete destruction of the test bacteria was not accomplished. When NaCl and Boric acid were removed from the hides with the first soaking process, bacteria on the hides may damage the hides during a long main soaking process. As a conclusion, more effective antibacterial treatments should be applied to fresh hides to completely destroy proteolytic and lipolytic bacteria on hides.
Keywords: TANNING PROCESSES; AEROBIC BACTERIA; PRESERVATION; MICROBIOLOGY